Full genomic sequence of the HLA‐DRB3*02:22:01 allele by single molecule real‐time sequencing technology. (18th June 2022) - Liacini, Abdelhamid; Dadkhodaie, Fereshte; Peters, Lindsey; Mathew, Leena; Geier, Steven
Abstract : Full‐length sequence covers the 5′‐untranslated region (UTR), all introns and exons, and the 3′ UTR.